2020
DOI: 10.29390/cjrt-2020-029
|View full text |Cite
|
Sign up to set email alerts
|

Pre-operative patient optimization to prevent postoperative pulmonary complications—Insights and roles for the respiratory therapist: A narrative review

Abstract: Background: The preoperative period has gained recognition as a crucial time to identify and manage preoperative medical conditions for preventing perioperative complications. Consequently, preoperative clinics have now become an essential component of perioperative care at many large hospitals. As the prevalence of preoperative clinics continues to grow, and the field of perioperative medicine progresses, respiratory therapists (RTs) will inevitably find a growing role to participate in preoperative patient o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 35 publications
0
3
0
1
Order By: Relevance
“…For thoracic surgery, PPCs are the most common complications that pose a threat to patients’ perioperative safety and affect their prognosis. Previous study has identified advanced age as a significant risk factor for the development of PPCs [ 18 , 19 ]. Specifically, elderly patients who undergo more invasive surgical procedures like lobectomy are at a heightened risk of experiencing PPCs.…”
Section: Discussionmentioning
confidence: 99%
“…For thoracic surgery, PPCs are the most common complications that pose a threat to patients’ perioperative safety and affect their prognosis. Previous study has identified advanced age as a significant risk factor for the development of PPCs [ 18 , 19 ]. Specifically, elderly patients who undergo more invasive surgical procedures like lobectomy are at a heightened risk of experiencing PPCs.…”
Section: Discussionmentioning
confidence: 99%
“…Namun dalam implementasinya ditemukan peningkatan data penjadwalan ulang atau pembatalan tindakan operasi akibat beberapa hal diantaranya kondisi pasien tidak layak operasi akibat persiapan operasi yang tidak optimal sebanyak 5.6% dalam 3 bulan terakhir. Waktu pelayanan yang cepat dan tepat serta load pasien yang tinggi menyebabkan pemberian edukasi persiapan operasi di rawat jalan menjadi tantangan bagi perawat (Schwartz et al, 2020). Berdasarkan hal tersebut, dibutuhkan penelitian yang memberikan gambaran perihal implementasi edukasi preoperatif di rumah sakit serta upaya solusi alternatif yang dapat memberikan dampak positif pada kepuasan pasien.…”
Section: Pendahuluanunclassified
“…De entre as complicações pós-operatórias mais frequentes, as complicações do foro pulmonar assumem uma prevalência entre 1% a 23% (Miskovic & Lumb, 2017;Odor et al, 2020). Caracterizam-se como disfunções não intencionais na função pulmonar no período pós-operatório, que influenciam a recuperação da pessoa submetida a cirurgia e são mais comuns em cirurgias aos segmentos torácico e abdominal (Liu et al, 2020;Lohiya et al, 2018;Lumb, 2019;Schwartz et al, 2020). Mais frequentemente manifestam-se por hipoxemia, atelectasia, pneumonia, broncospasmo, derrame pleural, embolia pulmonar, edema pulmonar, pneumotórax, falência respiratória e infeções (Ávila & Fenili, 2017;Kendall et al, 2018;Schwartz et al, 2020).…”
Section: Enquadramento Teóricounclassified